A construct validation of the tagasalo personality using the Panunukat ng Pagkataong Pilipino (PPP). [article]. - Go Tian, Rizason L. .
This study sought to run a criterion validation of the Tagasalo Scale using the Pnunukat ng Pagkataong Pilipino(PPP)as criterion. The study also sought to investigate gender as a significant variable. The scale were administered to 212 sophomore students(107 males, 105 females) taking General Psychology (age range=17-19 years old). Statistical analyses were performed and three factors of the tagasalo trait emerged:Dependability and Affiliation(DA), Anxiety in Social Situation (AnxSS), and Responsibility(Resp.). Correlations between factors of the scale and PPP dimensions were small to moderate. Validation of the scale was not established but the gender variable was significant in that females showed higher tagasalo trait than males did.